Answer

Verified

458.1k+ views

Hint: Apply the formula,

$\int\limits_{a}^{b}{f\left( x \right)dx=\left( b-a \right)\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ f\left( a \right)+f\left( a+h \right)+......+f\left( a+\left( n-1 \right)h \right) \right]}$, where $h=\dfrac{b-a}{n}.$

The given integral is

$\int\limits_{0}^{2}{{{e}^{x}}dx}$

By definition integral as limit of sum can be written as,

$\int\limits_{a}^{b}{f\left( x \right)dx=\left( b-a \right)\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ f\left( a \right)+f\left( a+h \right)+....+f\left( a+\left( n-1 \right)h \right) \right]}$, where $h=\dfrac{b-a}{n}$

So, when we are converting an integral to a limit of sum we use the above formula.

Here \[f\left( x \right)\] is the function to be integrated with \[a\] as lower limit and \[b\] as upper limit.

The right hand side is the conversion to limit.

In this question our function is $'{{e}^{x}}'$ with \[0\] as lower limit and \[2\] is upper limit.

So, we get

$\int\limits_{0}^{2}{{{e}^{x}}dx=\left( 2-0 \right)\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ {{e}^{0}}+{{e}^{\left( o+h \right)}}+....+{{e}^{\left( o+\left( n-1 \right)h \right)}} \right]}.......\left( i \right)$

Now here we will find the value of ‘$h$ ‘.

$h=\dfrac{b-a}{n}$

Substituting the values of upper and lower limit, we get

$h=\dfrac{2-0}{n}=\dfrac{2}{n}..........\left( ii \right)$

Now substituting the value of the equation$\left( ii \right)$ in equation $\left( i \right)$ , we get

$\int\limits_{0}^{2}{{{e}^{x}}dx=2\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ {{e}^{0}}+{{e}^{\left( o+\dfrac{2}{n} \right)}}+....+{{e}^{\left( o+\left( n-1 \right)\dfrac{2}{n} \right)}} \right]}$

We know ${{e}^{0}}=1$ , so the above equation becomes,

$\int\limits_{0}^{2}{{{e}^{x}}dx=2\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ 1+{{e}^{\left( \dfrac{2}{n} \right)}}+....+{{e}^{\dfrac{2}{n}\left( n-1 \right)}} \right]}...........\left( iii \right)$

Now consider the series,

$1+{{e}^{\left( \dfrac{2}{n} \right)}}+.....+{{e}^{\dfrac{2}{n}\left( n-1 \right)}}.........\left( iv \right)$

This is an geometric progression (GP) series with first term as ${{e}^{\left( \dfrac{2}{n} \right)}}$ , common ratio as ‘${{e}^{\dfrac{2}{n}}}$ ‘

Here we can also observe that there are ‘$n$’ terms in the series.

Now the sum of first $n$ terms of a $GP$ is

${{s}_{n}}=\dfrac{a\left( {{r}^{n}}-1 \right)}{r-1},r>1$

Where ‘$a$‘ is the first term, ‘$n$ ‘ is the number of terms and ‘$r$ ‘ is the common ratio.

Applying this formula in equation $\left( iv \right)$ series, we get

${{s}_{n}}=\dfrac{1\left( {{e}^{{{\left( \dfrac{2}{n} \right)}^{n}}-1}} \right)}{\left( {{e}^{\dfrac{2}{n}}}-1 \right)}$

${{s}_{n}}=\left( \dfrac{{{e}^{2}}-1}{{{e}^{\dfrac{2}{n}}}-1} \right)$

Substituting this value in equation $\left( iii \right)$ we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left( \dfrac{{{e}^{2}}-1}{{{e}^{\dfrac{2}{n}}}-1} \right)$

Taking out the constant term, we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\underset{n\to \infty }{\mathop{\lim }}\,\left( \dfrac{1}{\dfrac{{{e}^{\dfrac{2}{n}}}-1}{\dfrac{1}{n}}} \right)$

Now we will multiply and divide by $'2'$ in denominator, we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\underset{n\to \infty }{\mathop{\lim }}\,\left( \dfrac{1}{2\left[ \dfrac{{{e}^{\dfrac{2}{n}}}-1}{\dfrac{2}{n}} \right]} \right).........(iv)$

We know the formula,

$\underset{t\to 0}{\mathop{\lim }}\,\dfrac{{{e}^{t}}-1}{t}=1$

We know, as $n\to \infty $ then $\dfrac{2}{n}\to 0$ .

So, the denominator can be written as,

$\underset{\dfrac{2}{n}\to 0}{\mathop{\lim }}\,\dfrac{{{e}^{\dfrac{2}{n}}}-1}{\dfrac{2}{n}}=1$

Substituting this value in the equation (iv), we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\underset{n\to \infty }{\mathop{\lim }}\,\left( \dfrac{1}{2(1)} \right)$

As this is free from $'n'$ term so the value remain same even after applying the limit, so the above equation can be written as,

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\left( \dfrac{1}{2} \right)=({{e}^{2}}-1)$

Hence this is the required integral value.

Note: Student might get confused looking at the series $1+{{e}^{\left( \dfrac{2}{n} \right)}}+.....+{{e}^{\dfrac{2}{n}\left( n-1 \right)}}$.

They might take this as an arithmetic progression series. If we apply the AP series formula, we will get the wrong answer.

$\int\limits_{a}^{b}{f\left( x \right)dx=\left( b-a \right)\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ f\left( a \right)+f\left( a+h \right)+......+f\left( a+\left( n-1 \right)h \right) \right]}$, where $h=\dfrac{b-a}{n}.$

The given integral is

$\int\limits_{0}^{2}{{{e}^{x}}dx}$

By definition integral as limit of sum can be written as,

$\int\limits_{a}^{b}{f\left( x \right)dx=\left( b-a \right)\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ f\left( a \right)+f\left( a+h \right)+....+f\left( a+\left( n-1 \right)h \right) \right]}$, where $h=\dfrac{b-a}{n}$

So, when we are converting an integral to a limit of sum we use the above formula.

Here \[f\left( x \right)\] is the function to be integrated with \[a\] as lower limit and \[b\] as upper limit.

The right hand side is the conversion to limit.

In this question our function is $'{{e}^{x}}'$ with \[0\] as lower limit and \[2\] is upper limit.

So, we get

$\int\limits_{0}^{2}{{{e}^{x}}dx=\left( 2-0 \right)\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ {{e}^{0}}+{{e}^{\left( o+h \right)}}+....+{{e}^{\left( o+\left( n-1 \right)h \right)}} \right]}.......\left( i \right)$

Now here we will find the value of ‘$h$ ‘.

$h=\dfrac{b-a}{n}$

Substituting the values of upper and lower limit, we get

$h=\dfrac{2-0}{n}=\dfrac{2}{n}..........\left( ii \right)$

Now substituting the value of the equation$\left( ii \right)$ in equation $\left( i \right)$ , we get

$\int\limits_{0}^{2}{{{e}^{x}}dx=2\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ {{e}^{0}}+{{e}^{\left( o+\dfrac{2}{n} \right)}}+....+{{e}^{\left( o+\left( n-1 \right)\dfrac{2}{n} \right)}} \right]}$

We know ${{e}^{0}}=1$ , so the above equation becomes,

$\int\limits_{0}^{2}{{{e}^{x}}dx=2\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left[ 1+{{e}^{\left( \dfrac{2}{n} \right)}}+....+{{e}^{\dfrac{2}{n}\left( n-1 \right)}} \right]}...........\left( iii \right)$

Now consider the series,

$1+{{e}^{\left( \dfrac{2}{n} \right)}}+.....+{{e}^{\dfrac{2}{n}\left( n-1 \right)}}.........\left( iv \right)$

This is an geometric progression (GP) series with first term as ${{e}^{\left( \dfrac{2}{n} \right)}}$ , common ratio as ‘${{e}^{\dfrac{2}{n}}}$ ‘

Here we can also observe that there are ‘$n$’ terms in the series.

Now the sum of first $n$ terms of a $GP$ is

${{s}_{n}}=\dfrac{a\left( {{r}^{n}}-1 \right)}{r-1},r>1$

Where ‘$a$‘ is the first term, ‘$n$ ‘ is the number of terms and ‘$r$ ‘ is the common ratio.

Applying this formula in equation $\left( iv \right)$ series, we get

${{s}_{n}}=\dfrac{1\left( {{e}^{{{\left( \dfrac{2}{n} \right)}^{n}}-1}} \right)}{\left( {{e}^{\dfrac{2}{n}}}-1 \right)}$

${{s}_{n}}=\left( \dfrac{{{e}^{2}}-1}{{{e}^{\dfrac{2}{n}}}-1} \right)$

Substituting this value in equation $\left( iii \right)$ we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2\underset{n\to \infty }{\mathop{\lim }}\,\dfrac{1}{n}\left( \dfrac{{{e}^{2}}-1}{{{e}^{\dfrac{2}{n}}}-1} \right)$

Taking out the constant term, we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\underset{n\to \infty }{\mathop{\lim }}\,\left( \dfrac{1}{\dfrac{{{e}^{\dfrac{2}{n}}}-1}{\dfrac{1}{n}}} \right)$

Now we will multiply and divide by $'2'$ in denominator, we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\underset{n\to \infty }{\mathop{\lim }}\,\left( \dfrac{1}{2\left[ \dfrac{{{e}^{\dfrac{2}{n}}}-1}{\dfrac{2}{n}} \right]} \right).........(iv)$

We know the formula,

$\underset{t\to 0}{\mathop{\lim }}\,\dfrac{{{e}^{t}}-1}{t}=1$

We know, as $n\to \infty $ then $\dfrac{2}{n}\to 0$ .

So, the denominator can be written as,

$\underset{\dfrac{2}{n}\to 0}{\mathop{\lim }}\,\dfrac{{{e}^{\dfrac{2}{n}}}-1}{\dfrac{2}{n}}=1$

Substituting this value in the equation (iv), we get

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\underset{n\to \infty }{\mathop{\lim }}\,\left( \dfrac{1}{2(1)} \right)$

As this is free from $'n'$ term so the value remain same even after applying the limit, so the above equation can be written as,

$\int\limits_{0}^{2}{{{e}^{x}}}dx=2({{e}^{2}}-1)\left( \dfrac{1}{2} \right)=({{e}^{2}}-1)$

Hence this is the required integral value.

Note: Student might get confused looking at the series $1+{{e}^{\left( \dfrac{2}{n} \right)}}+.....+{{e}^{\dfrac{2}{n}\left( n-1 \right)}}$.

They might take this as an arithmetic progression series. If we apply the AP series formula, we will get the wrong answer.

Recently Updated Pages

What number is 20 of 400 class 8 maths CBSE

Which one of the following numbers is completely divisible class 8 maths CBSE

What number is 78 of 50 A 32 B 35 C 36 D 39 E 41 class 8 maths CBSE

How many integers are there between 10 and 2 and how class 8 maths CBSE

The 3 is what percent of 12 class 8 maths CBSE

Find the circumference of the circle having radius class 8 maths CBSE

Trending doubts

One cusec is equal to how many liters class 8 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Which are the Top 10 Largest Countries of the World?

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE